Analysis of factors influencing colostomy closure after low anterior resection for cancer rectum - Das, Prafulla Kumar; Satpathy, Bharat Bhusan (International Journal of Research in Medical Sciences, 2017)
Background: De-functioning colostomy or ileostomy is a procedure known worldwide as a protection measure to the rectal anatomises in low anterior resections and even some of anterior resections. Though the primary intention is a temporary one, many a times they end up in a permanent stoma. As the patients with stomas with attached bag appliances to their abdominal wall go through a lot of stress related to the quality of life and body image, they are always keen to get it closed as early as possible. Unfortunately, many factors come into play during and after the indexed surgery till the closure of stoma without any complication, prohibiting their early or even delayed closure. Methods: Authors here conducted a cohort study with retrospective data analysis and a prospective follow up patients in a tertiary care regional cancer centre from April 2011 to mid-June 2017. Statistical analysis was used by mean and percentage method. Results: Temporary colostomy was required in 88.37% of low anterior resections and some anterior resections. Most of those (92.11%) were transverse colostomy. Only 36.86% of those stomata were reversed. Four (10.83%) patients were dead by the end of the study. Twenty patients of stoma (52.63%) were not yet reversed and were deemed to continue with a permanent colostomy. This was found to be a very high figure as opposed to the literature of 9-25%. The reason behind this high figure was probably due to low general condition, lower socio-economic status, and low literacy prevailing in our patient population group. Moreover, the patient attendants and the surgeon himself also had played some role responsible for this situation. Conclusions: Patients should be told before initial rectal surgery that there is a risk of non-closure and possible complications associated with permanent stoma.